Daya Tarik Wisata dan Promosi Instagram Yang Memengaruhi Keputusan Berkunjung Wisatawan di The Ranch Cisarua - Alian, Muhammad Rifki; Siregar, Mariana R. A.; Santriani, Imani (JURNAL DESTINASI PARIWISATA, 2022)
The development of tourism in the future will face increasingly fierce competition in both marketing and tourism product development. A place that can be said as a tourist destination is certainly supported by various things, one of which is a tourist attraction and promotion on social media as an information tool. A tourist attraction is an interesting and worthy tourist place to visit. In addition to tourist attractions, promotions on social media can attract the attention of customers to visit tourist attractions. However, Tourist Attractions and Instagram Promotions require a maximum strategy so that the information provided can be given correctly and maximally. The Ranch Cisarua experienced a decrease in visitors in 2021 by 35 percent and the management of Instagram social media is still not optimal. Based on this, the purpose of this study was to determine the effect of tourist attraction and Instagram promotion on the decision to visit The Ranch Cisarua. This research is a type of quantitative research. The research was conducted at The Ranch Cisarua. The sampling technique is non-probability sampling with purposive sampling type. The number of samples of 100 people was taken from the total population of Instagram followers @theranchcisarua as many as 11,300 people. Data collection techniques using questionnaires and observation. The results of data analysis and it is known that there is an influence of tourist attraction and Instagram promotion on the decision to visit The Ranch Cisarua by 64 percent. Meanwhile, 36 percent is influenced by other variables not examined in this study. Keywords: Tourist Attractions, Visiting Decisions, Instagram Promotions, Publicity.